Política habitacional em zonas urbanas: o caso do conjunto habitacional Vila da Barca, em Belém - Almeida, Evandro Mauro Dias de (2010)
This thesis is the outcome of the research accomplished during the Master degree in Business Management program at the School of Public and Private Administration of the Getulio Vargas Foundation. This study investigated the production space in the city of Belém, just over the district of Vila da Barca, on the banks of the Guajará Bay. Some of the residents of Vila da Barca were relocated for another area by the Project for Housing and Urbanization, which is the public housing policy for the site established by the Municipal Government of Belém in partnership with the Brazilian Federal Government. The Secretaria Municipal de Habitação - SEHAB is the municipal institution in charge to apply the policy and to run the project. This research studies the housing project of Vila da Barca in order to identify the design process of the buildings, the relocation and the resettlement of the families, and the development of the urban space in the area. The methodology was developed using two main tools. Firstly, the residents were requested to answer a survey about their conditions. Secondly, interviews were done with professionals and technicians responsible for the project, such as: the Manager of Urban Development (GIDUR), Social and Technical Engineers, as well as, ofticials of the Federal Savings Bank in Belém. The research reports the opinion of the professionals interviewed, analyses the urban space production on its several aspects, studies some of the elements in the building process of the area, and finally, critics the outcomes of the project. The thesis advocates that society ought to build better and more efticient forms to supervise the government whenever the latter is implementing a program like the one at Vila da Barca, exercising not only the control of the government by the society but also the controlling mechanisms of the market. This control is the biggest contemporary challenge.